N–O Cleavage reactions of heterobicycloalkene-fused 2-isoxazolines - Nagireddy, Jaipal R.; Tranmer, Geoffrey K.; Carlson, Emily; Tam, William (Beilstein Journal of Organic Chemistry, 2014)
Transition metal-mediated N–O bond cleavage reactions of heterobicycloalkene-fused 3-methyl-2-isoxazolines were investigated. Optimal cleavage conditions were found with Raney nickel/AlCl3 mediation in aqueous methanol. The reaction provided a diverse collection of novel heterobicycle-fused β-hydroxyketones with good to excellent yields (66–95%) and without the need for chromatographic purification.
Keywords: azabicycloalkene; β-hydroxyketone; 2-isoxazoline; oxabicycloalkene; Raney nickel

(untitled) - Nitta, M.; Kobayashi, T. (J. Chem. Soc., Perkin Trans. 1, 1984)

(untitled) - Curran, D. P.; Fenk, C. J. (Tetrahedron Lett., 1986)

(untitled) - Pohjakallio, A.; Pihko, P. M.; Liu, J. (J. Org. Chem., 2010)

(untitled) - Gelabert, L. I.; Fascio, M. L.; D’Accorso, N. B. (J. Heterocycl. Chem., 2003)

(untitled) - Kozikowski, A. P. (Acc. Chem. Res., 1984)

(untitled) - Burri, K. F.; Cardone, R. A.; Chen, W. Y.; Rosen, P. (J. Am. Chem. Soc., 1978)

(untitled) - Nagireddy, J. R.; Raheem, M.-A.; Haner, J.; Tam, W. (Curr. Org. Synth., 2011)

(untitled) - Bull, J. A.; Balskus, E. P.; Horan, R. A. J.; Langner, M.; Ley, S. V. (Chem.–Eur. J., 2007)

(untitled) - Das, B.; Satyakumar, A.; Ravikanth, B.; Rao, B. V.; Raju, T. V.; Siddhardha, B.; Murty, U. S. (J. Heterocycl. Chem., 2013)

(untitled) - Bode, J. W.; Carreira, E. M. (J. Am. Chem. Soc., 2001)

(untitled) - Litvinovskaya, R. P.; Koval’, N. V.; Khripach, V. A. (Chem. Heterocycl. Compd., 2000)

(untitled) - Curran, D. P. (J. Am. Chem. Soc., 1983)

(untitled) - Jiang, B.; Liu, Y.; Zhou, W.-s. (J. Org. Chem., 2000)

(untitled) - Barco, A.; Benetti, S.; De Risi, C.; Pollini, G. P.; Zanirato, V. (Tetrahedron, 1995)

(untitled) - Andersen, S. H.; Sharma, K. K.; Torssell, K. B. G. (Tetrahedron, 1983)

(untitled) - Jäger, V.; Grund, H. (Angew. Chem., Int. Ed. Engl., 1976)

(untitled) - Bode, J. W.; Carreira, E. M. (Org. Lett., 2001)

(untitled) - Baraldi, P. G.; Barco, A.; Benetti, S.; Manfredini, S.; Simoni, D. (Synthesis, 1987)

(untitled) - Baraldi, P. G.; Bigoni, A.; Cacciari, B.; Caldari, C.; Manfredini, S.; Spalluto, G. (Synthesis, 1994)

(untitled) - Tranmer, G. K.; Tam, W. (Org. Lett., 2002)

(untitled) - Nagireddy, J. R.; Carlson, E.; Tam, W. (Can. J. Chem., 2014)

(untitled) - Asaoka, M.; Mukuta, T.; Takei, H. (Tetrahedron Lett., 1981)

(untitled) - King, G. S.; Magnus, P. D.; Rzepa, H. S. (J. Chem. Soc., Perkin Trans. 1, 1972)

(untitled) - Jiang, D.; Chen, Y. (J. Org. Chem., 2008)

(untitled) - Kozikowski, A. P.; Adamczyk, M. (Tetrahedron Lett., 1982)

(untitled) - Bondar, N. F.; Isaenya, L. P.; Skupskaya, R. V.; Lakhvich, F. A. (Russ. J. Org. Chem., 2003)

(untitled) - Lough, A. J.; Nagireddy, J. R.; Tam, W. (Acta Crystallogr., Sect. E, 2014)